Retrospective efficacy analysis of stellate ganglion block combined with general anesthesia in arthroscopic shoulder surgery: a cohort study - Pan, Zilin; Li, Jiawei; Xu, Yizhen; Yuan, Yingchuan (Frontiers in Medicine, 2025)
PurposeAlthough arthroscopic shoulder surgery confers clear advantages for recovery, it is often complicated by intraoperative hemodynamic instability and prolonged postoperative pain. This study investigates the clinical utility of stellate ganglion block (SGB) combined with general anesthesia (GA) to address these issues.MethodsIn this retrospective analysis, 60 patients undergoing elective shoulder arthroscopy were categorized into SGB+GA (n = 30) and GA-only (n = 30) cohorts. Outcomes included intraoperative hemodynamic parameters (MAP, HR), postoperative pain (VAS scores), opioid-related complications, and hospitalization duration. Statistical analyses utilized t-tests and non-parametric tests.ResultsThe SGB+GA group demonstrated superior hemodynamic stability (P < 0.001) and markedly lower pain scores postoperatively (P < 0.001). Opioid-induced complications such as nausea (P = 0.028) were significantly reduced. Median hospital stay was shorter with SGB+GA (P < 0.001).ConclusionIntegrating SGB with GA optimizes perioperative management by stabilizing hemodynamics, enhancing analgesia, and minimizing opioid reliance, thereby expediting recovery. These findings support SGB as a valuable adjunct, though prospective validation is needed.